Refining the chronology for west polynesian colonization: New data from the Samoan archipelago. (April 2016) - Clark, Jeffrey T.; Quintus, Seth; Weisler, Marshall; St Pierre, Emma; Nothdurft, Luke; Feng, Yuexing
Abstract: The timing and unprecedented speed of the Lapita migration from the western edge of Oceania to western Polynesia in the Central Pacific have long been of interest to archaeologists. The eastern-most extent of that great human migration was the Samoan Archipelago in West Polynesia, although critical questions have remained about the timing and process of Samoan colonization. To investigate those questions, we carried out a Bayesian analysis of 19 radiocarbon dates on charcoal and 8 uranium-thorium (U-Th) series coral dates from four archaeological sites on Ofu Island in the eastern reaches of Samoa. The analysis indicates initial settlement of Ofu at 2717–2663 cal BP (68.2%) by people using Plainware rather than the diagnostic dentate-stamped Lapita pottery. This date range indicates that there is not a significant chronological gap between Lapita and Plainware sites in Samoa, which holds implications for modeling the settlement process in the Central Pacific. Highlights: Bayesian analysis of 19 14 C charcoal and 8 U-series coral dates from Samoa Colonization of Ofu Island at 2717–2663 cal BP (68.2%)/2774–2647 cal BP (95.4%) There is no significant time gap between Lapita and Plainware sites in Samoa Refutes a demographically driven model for colonization of West Polynesia Settlement of Ofu was soon after the loss of decorated Lapita pottery in Tonga